New perspectives in the treatment of GIST - Valadão, Marcus (2006)
The insight gained in recent years concerning the molecular pathogenesis of gastrointestinal stromal tumor (GIST) has led to advances in knowledge about its diagnosis and treatment. Only recently has GIST been understood as a distinct clinical entity, with its biological features and natural history recognized. Historically, surgery was the only effective treatment. However, surgical outcome was disappointing, since only 30-40% of patients were cured after long-term follow-up. The discovery of imatinib benefited patients with metastatic and unresectable disease, providing hopeful results and bringing new perspectives that its combined use with surgery could improve outcome and increase the probability of cure.